2024
DOI: 10.3389/fpubh.2023.1244358
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of highly resistant Candida auris in the United Arab Emirates: a retrospective analysis of evolving national trends

Jens Thomsen,
Najiba M. Abdulrazzaq,
Abderrahim Oulhaj
et al.

Abstract: IntroductionThe Centers for Disease Prevention and Control lists Candida auris, given its global emergence, multidrug resistance, high mortality, and persistent transmissions in health care settings as one of five urgent threats. As a new threat, the need for surveillance of C. auris is critical. This is particularly important for a cosmopolitan setting and global hub such as the United Arab Emirates (UAE) where continued introduction and emergence of resistant variant strains is a major concern.MethodsThe Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…[34,35]. The recent study published by Thomsen et al [31] revealed alarming trends in the resistance patterns of C. auris in the UAE, analyzing 908 C. auris isolates from the 2018-2021 observation period and offered some demographic data associated with C. auris infection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[34,35]. The recent study published by Thomsen et al [31] revealed alarming trends in the resistance patterns of C. auris in the UAE, analyzing 908 C. auris isolates from the 2018-2021 observation period and offered some demographic data associated with C. auris infection.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in median of length of hospitalization between both groups was also statistically significant, with patients associated with C. auris infections accumulating a median length of stay of 33.5 days as opposed to 14 days for patients associated with non-auris Candida infections. Thomsen J et al also calculated a mortality rate of 27.5% from a subset of patients with known admission and discharge dates in the C. auris group (47/171 patients) [31].…”
Section: Extrapolation)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, outbreaks of C. auris among severely ill COVID-19 patients during the peak of the pandemic were only observed in certain countries, such as Italy and the USA [21]. An epidemiological analysis conducted during the pandemic in the United Arab Emirates found an increase in COVID-19 and C. auris co-infection in hospitals with overwhelmed intensive care units [57]. Patients had significant underlying comorbidities and were treated with broad-spectrum antibiotics and immunosuppressive therapies.…”
Section: Auris and Covid-19mentioning
confidence: 99%